Bipolar disorder and aging - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2023)
Bipolar disorder is a chronic illness, defined by a succession of depressive and/or manic periods separated by free intervals. Its evolution with aging is marked by a high suicide mortality rate. Bipolar disorders raise the question of their evolution when the age of the subject, in particular with regard to their frequency, their clinical characteristics, their prognosis and their management. The evolution of bipolar disorder with aging poses several difficulties in clinical practice due to its underestimated frequency and its misleading presentation and in particular by the presence of sometimes significant cognitive alterations leading sometimes to dementia.